(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2019)
In the year 2030, there will be a megalopolis of 52 million inhabitants, larger than the population of Colombia. In 2050, there will be another 130 million people, the same as all of Mexico today. They’ll both be in China. The first is located in the Pearl River Delta and will be 26 times bigger than the Greater London, and the second, around Beijing and will be called JingJinJi, with 212,000 km2. The planet is plagued by similar phenomena that configures a challenge to human creativity. Soon, three quarters of the population will live in urban spaces. The other quarter will depend on the other three. How did homo sapiens come to this level of complexity? What are his challenges? The two questions are at the centre of this reflection that seeks to understand the city as a complex dynamic system based on history.